PENGARUH HARGA, KUALITAS PRODUK DAN GRUP REFERENSI TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN SECARA ONLINE (STUDI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA PONTIANAK) - B31111041, Esti Agustina Silitonga (Jurnal Manajemen Update, 2016)
The development of internet technology has increased every year including in Indonesia. It is utilized by the market to sell their products online. Many online stores that sell clothing, this is because clothing is a primary requirement for any person so as to make this product can be sold easily online. The purpose of this research is to know the influence of the price, the quality of the product and the reference group against the decision of purchase apparel online. Population in this study is the student of Faculty of Economics University of Tanjungpura Pontianak ever do purchase apparel online. The sample in this study amounts to 100 people. Sampling using a purposive sampling technique. Data collection instruments use a likert scale measurement with a questionnaire that has qualified the validity and reliability. Tools of analysis used in this study is the analysis of multiple linear regression, then conducted a partial test of significance with the results of the variable price do not affect the significance of the purchase apparel online. Based on the test of significance is known that the variable quality of products and reference group influential significance against the decision of purchase apparel online, viewed from the regression coefficient for each variable < 0,05 (5%). Keywords: Price, Quality of the Products, Reference Group, Purchase Decision